Penerapan Marketing Mix Syariah Penerapan Marketing-Mix Syariah pada Inovasi Produk Soya Stick Dari Limbah Kulit Ari Kedelai dan Umbi Porang - Krisanti, Aulia Arum; Susilowati, Fitriah Dwi (Jurnal Ekonomika dan Bisnis Islam, 2024)
This research aims to determine the application of Sharia Marketing Mix in Soya Stick Product Innovation (SOTICK) which is made from soybean husk waste and porang tubers which are rich in protein. This research uses a qualitative research method with a literature review method. With data from book literature sources, journal articles from research or sources related to the topic of discussion in the last 5 years. To then be analyzed and classified according to valid facts and data. The result of this research is the application of sharia marketing mix to Soya Stick product innovation which consists of product, price, location, promotion, people, process and physical evidence. The sharia marketing mix is ??in accordance with the conditions and plans of the Soya Stick idea. Where Soya Stick's vision is to provide benefits that suit people's needs and can be marketed widely. Therefore, it is necessary to apply sharia marketing mix in Soya Stick product development so that the product objectives can be implemented properly in accordance with Islamic economic principles, namely the benefit that prioritizes the general interest, rather than the interests of certain individuals or groups..